Subvenções tributárias: análises sintática, semântica e pragmática - Félix, Talita Pimenta (2019)
This work aims at the study of the so-called tax subsidies and proposes to go through its linguistic aspects relevant to the syntactic, semantic and pragmatic fields of the tax legal regime related to such subsidies. In doing so, we aim to answer some fundamental questions on the subject: i. what are tax subsidies, which is a problem related to semantics and goes through the analysis of the relationship that is established between a purpose, a norm and a intervention in the economic domain that is effective through this standard; ii. how the rules granting tax jurisdiction for exemptions are structured, as well as those granting exemptions, which is a syntax-related problem; and iii. what is the relationship between grants and the Corporate Income Tax and how this link is handled by our courts and legislation, here, connected to pragmatics. The answer to these three questions is the central axis of this work. However, as such questions are answered, new inferences are illuminated by reason, so small "theses" are woven throughout the text, in a game of implications that the firm consolidation of premises and subsequent conclusions allows us Employ. As a method of work, we will adopt logical-semantic constructivism, which is a line of approximation of positive right by requiring the interpreter to tie concepts, clarifying the premises that allow appropriate control to the examination of discourse Scientific. Precisely because of the method, the choice of themes was conditioned in an orderly manner, according to certain epistemological needs. Thus, initially, a study will be developed of propaedeutic issues essential to the Science and demarcation of its object. And here, we will adopt the clear premise that communication is right and how it should be treated. Next, we'll get into semantic issues. We are aware that it is not usual to deal with semantics before syntax, since semiotics usually invites an initial syntactic examination. However, as the method of logical-semantic constructivism imposes on us the definition of concepts, we note that we could not outline an adequate syntax of the norm of dishonorable competence or of the norm that institutes exemption, without an adequate demarcation of the concept of subsidy, among others. Once the semantic effort is overcome, we will enter the syntax. There, by presenting a small theory about the logical structure of the exemption standard, and the competence of the exemption standard, we will be able to rich inferences on the subject of subsidies